Pengaruh sektor industri halal terhadap pertumbuhan ekonomi di 15 negara top global ekonomi - May Husnul Khotimah; Dina Oktaviani; Munajar Munajar (Nur Science Institute, 2026)
This study examines the role of the halal industry in promoting economic growth across the top 15 global countries listed in the State of the Global Islamic Economy Index (SGIEI). The research gap arises from inconsistencies in previous empirical findings on the contribution of each halal industry subsector to economic growth, as well as from the limited number of studies that integrate all major subsectors using recent data. A quantitative approach is employed using secondary panel data covering six halal industry subsectors: halal food, Islamic finance, Muslim-friendly tourism, modest fashion, halal pharmaceuticals and cosmetics, and media and recreation, during the 2023–2024 period in the top 15 global economy countries. The data are obtained from the State of the Global Islamic Economy (SGIEI) and the World Bank. Panel data regression analysis is applied, with the Random Effect Model (REM) selected as the most appropriate estimation model. The findings indicate that the halal food and Muslim-friendly tourism subsectors have a positive and significant impact on economic growth. In contrast, the other halal industry subsectors do not demonstrate a statistically significant effect.